Prospective evaluation of oral cannabis extracts in children with epilepsy - Knupp, Kelly G.; Rice, John D.; Helmkamp, Laura J.; Galinkin, Jeffrey; Sempio, Cristina; Jost, Klawitter; Chapman, Kevin E. (Seizure (London, England), 2019)
•Doses of OCE used are lower than used in randomized trials.•Response rates to OCE was 24%.•14% stopped OCE use due to increased seizures.•Levels of THC-COOH and CBD did not correlate with response. Interest in the use of artisanal cannabinoids in pediatric epilepsy has increased but safety and utility data are lacking. Our aim was to prospectively characterize the use of oral cannabis extracts (OCE) in a refractory pediatric epilepsy population. Families considering the use of an OCE were enrolled in a prospective observational study. Baseline seizure frequency was assessed over a period of 4 weeks. Seizure frequency, CBD and THC-COOH levels were assessed every 4 weeks during a 12-week treatment period. Response was defined as at least a 50% reduction in seizure frequency over the final 8 weeks of the study relative to baseline. Consent was obtained in 32 children; 11 were excluded from analysis (3 failed to complete baseline data, 3 started OCE before completing baseline period and 5 did not start OCE) leaving 21 to be included in subsequent analyses. Median age was 10.3 years (IQR 6.8–12.6), 13 (62%) were male and median seizure frequency was 2.7 seizures/day during the baseline period. The median of the high dose of CBD that was administered during the observation period was of 0.9 (0.6–2.2) mg/kg/day. Of the 21 subjects who were included in the analysis, 5 (24%) were responders. OCE was stopped early in 3 subjects (14%) due to a perceived increase in seizures. THC-COOH and CBD blood levels did not have a significant association with response status (p = 0.95 CBD, p = 0.53 THC-COOH, N = 14). The observed response rate in this study is similar to placebo rates in prospective randomized trials of pharmaceutical grade products and the withdrawal rate is greater than rates obtained with retrospective methods. Doses of OCE administered were lower than doses used in randomized trials.